Navigating the complexities of advanced recycling: Processes, feedstock, and public health connections in the context of the global plastic pollution crisis - Matuch, Cindy; Chen, Wan‐Ting (Grace); Ternes, Mary Ellen; Seay, Jeffrey (Environmental progress & sustainable energy, 2025)
Plastic pollution is a pressing global issue, impacting both the environment and human health. The urgency of this challenge is underscored by the ongoing United Nations negotiations for a legally binding instrument on plastic pollution. Given the complexities of the plastic waste stream and recycling processes, exploring innovative solutions is crucial. Advanced recycling has been offered as a potential solution to combat the influx of plastic waste, and we examined its connections with post‐use plastic feedstock and human health, providing a neutral overview without endorsing any specific solutions. The debate on classifying these technologies as recycling highlights the need for universal definitions and transparency in waste management. Using the United States as a case study, different approaches to advanced recycling, their implementation status, and related policy gaps are compared. Simplified plastic formulations, transparent reporting on the environmental footprint of advanced recycling, and increased research investments may be needed to pave the way for a more sustainable future in plastic waste management. Insights obtained from this review will help non‐specialists, particularly policymakers, and relevant industry sectors understand the landscape of advanced recycling within the United States.